Separating symptomatic Alzheimer’s disease from depression based on structural MRI - Klöppel, Stefan; Hausner, Lucrezia; Frölich, Lutz; Förster, Alex (Journal of Alzheimer's disease, 2018)
Older patients with depression or Alzheimer’s disease (AD) at the stage of early dementia or mild cognitive impairment may present with objective cognitive impairment, although the pathology and thus therapy and prognosis differ substantially. In this study, we assessed the potential of an automated algorithm to categorize a test set of 65 T1-weighted structural magnetic resonance images (MRI).